2010
DOI: 10.1007/s10571-010-9516-x
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis-Induced Zinc-Dependent Death of Cultured Cerebellar Granule Neurons

Abstract: Severe acidosis caused death of cultured cerebellar granule neurons (CGNs). Acidosis was accompanied by a progressive increase of the intracellular zinc ions ([Zn(2+)](i)) and decrease of [Ca(2+)](i). Zn(2+) chelator, N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine (TPEN), prevented the increase of [Zn(2+)](i) and acidosis-induced neuronal death. However, neuronal death was insensitive to blockade of ASIC1 channels with amiloride, as CGNs display considerably lower expression of ASIC1a than other neurons. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…(2003) failed to observe any [Zn 2+ ] i elevations. In cultured cerebellar granule cells, Isaev et al. (2010) did observe [Zn 2+ ] i elevations under such conditions but the exposures lasted as long as 30 min.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…(2003) failed to observe any [Zn 2+ ] i elevations. In cultured cerebellar granule cells, Isaev et al. (2010) did observe [Zn 2+ ] i elevations under such conditions but the exposures lasted as long as 30 min.…”
Section: Resultsmentioning
confidence: 89%
“…2003). In cerebellar granule cells, [Zn 2+ ] i elevations were observed when the exposures to pH 6.0 were prolonged to 30 min (Isaev et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The study was made on 7 9 day old cultures of cerebellar granule neurons pre pared from the cerebella of 8 day old Wistar rats by enzyme-mechanical dissociation [10]. The cerebella were washed with Ca 2+ and Mg 2+ free phosphate buffer solution (PBS; Dulbecco) and incubated in the same solution containing 0.05% trypsin and 0.02% EDTA (15 min, 37°C).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that under condi tions of calcium ion imbalance, the accumulation of Zn 2+ in intracellular zinc stores is blocked by acidosis [9]. Extracellular acidosis is accompanied by a progressive increase of [Zn 2+ ] i in cerebellar granule neurons (CGNs) [10,11]. Mild acidosis enhances AMPA receptor medi ated intracellular zinc mobilization in cortical neurons [12].…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that acid‐induced neuronal death is preceded by elevations of intracellular [Zn 2+ ] ([Zn 2+ ] i ) (Isaev et al . ), which occur owing to a Zn 2+ release from intracellular stores (Sensi et al . ; Kiedrowski , ).…”
mentioning
confidence: 99%